Investigation of Feshbach resonances in ultracold (40)K spin mixtures - Krauser, J. S. (Phys Rev A (Coll Park), 2017)
Magnetically tunable Feshbach resonances are an indispensable tool for experiments with atomic quantum gases. We report on 37 thus far unpublished Feshbach resonances and four further probable Feshbach resonances in spin mixtures of ultracold fermionic (40)K with temperatures well below 100 nK. In particular, we locate a broad resonance at B = 389.7G with a magnetic width of 26.7 G. Here 1 G = 10(−4) T. Furthermore, by exciting low-energy spin waves, we demonstrate a means to precisely determine the zero crossing of the scattering length for this broad Feshbach resonance. Our findings allow for further tunability in experiments with ultracold (40)K quantum gases.